2013
DOI: 10.1590/0103-6440201302006
|View full text |Cite
|
Sign up to set email alerts
|

History of Chronic Periodontitis Is a High Risk Indicator for Peri-Implant Disease

Abstract: The success rates in implant dentistry vary significantly among patients presenting previous history of periodontitis. The aim of this study was to evaluate if patients with history of chronic periodontitis (CP) are more susceptible to peri-implant disease (PID) than those without history of CP. Two hundred and fifteen individuals, under periodontal maintenance, presenting 754 osseointegrated implants, were selected for this study. The patients were divided into two groups according to the peri-implant status:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 23 publications
3
54
0
5
Order By: Relevance
“…There is scientific evidence for an association between peri-implantitis and active periodontitis. 25 Casado et al 20 concluded that patients with a previous history of periodontal disease that had been treated and arrested had a four-fold higher risk of developing peri-implant disease. When all sample implants were taken, the present study finds a positive correlation between MBL and a previous history of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is scientific evidence for an association between peri-implantitis and active periodontitis. 25 Casado et al 20 concluded that patients with a previous history of periodontal disease that had been treated and arrested had a four-fold higher risk of developing peri-implant disease. When all sample implants were taken, the present study finds a positive correlation between MBL and a previous history of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Dvorak et al 17 and Máximo et al 18 have studied the correlation between peri-implantitis and osteoporosis, and their results are inconclusive. Periimplantitis might also be related to other factors, such as periodontal disease and guided bone regeneration (GBR) at the implant site, [19][20][21] and to other systemic diseases, such as diabetes 8 and cardiovascular disease. 22,23 The aims of this study are as follows: 1) to evaluate the possibility of a correlation between osteoporosis (MCI) and MBL and 2) to assess whether various systemic diseases, periodontitis, and placement of implants in regenerated bone are correlated with either MBL or MCI.…”
mentioning
confidence: 99%
“…Recently, chronic periodontitis (CP) was considered a major risk factor for impaired osseointegration process (3,4). Similar to periodontitis, in peri-implantitis, increased microbial activity can disrupt the balance of the host response, stimulating osteoclastic activity with consequent bone resorption and implant loss (5).…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of PID have been attributed to biomechanical failure resulting from bacterial infection and occlusal overload, in which the main risk factors are poor oral hygiene, smoking, diabetes mellitus, as well as periodontitis. The implant success rate in patients without a history of periodontitis is 96.5%, whereas in patients with a history of periodontitis it is 90.5% (1,2).…”
Section: Introductionmentioning
confidence: 99%